Impact of plasticity and stress history on thermal volume changes in clays - Hamed Hoseini Mighani; Saeed Tourchi; Arash Alimardani Lavasan; Fatemehsadat Hosseini; Janos Szendefy (Scientific Reports)
Abstract This endeavor explores fine-grained soils’ thermally induced volumetric behavior through a series of temperature-controlled oedometer experiments under drained conditions. Undisturbed clay samples were subjected to incremental heating and cooling to evaluate the effects of over-consolidation ratio (OCR), stress history, and soil plasticity. Results revealed that normally consolidated clays undergo significant plastic contraction during heating. Over-consolidated samples showed contraction-dominated responses, highlighting the limitations of OCR as a standalone predictor of thermal behavior, with stress history emerging as a key factor. Furthermore, the influence of soil plasticity was pronounced, with high-plasticity clays experiencing greater thermal contraction due to enhanced microstructural rearrangement and mineralogical effects. The heating and cooling cycle further highlighted the irreversibility of volumetric changes in normally consolidated states, while over-consolidated samples exhibited reduced thermal hysteresis. These findings offer a detailed understanding of thermally induced volume changes in fine-grained soils, revealing the interplay between stress state, consolidation history, and intrinsic soil properties. The insights gained are foundational for advancing predictive models, optimizing the design of thermally loaded geo-energy systems, and addressing climate-driven challenges such as soil-atmosphere interactions and landslide susceptibility.